2013
DOI: 10.1093/schbul/sbt105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subgroups of Schizophrenia Patients With Changes in Either Immune or Growth Factor and Hormonal Pathways

Abstract: Schizophrenia is a heterogeneous disorder normally diagnosed using the Diagnostic and Statistical Manual of Mental Disorders criteria. However, these criteria do not necessarily reflect differences in underlying molecular abnormalities of the disorder. Here, we have used multiplexed immunoassay analyses to measure immune molecules, growth factors, and hormones important to schizophrenia in acutely ill antipsychotic-naive patients (n = 180) and matched controls (n = 398). We found that using the resulting molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 40 publications
7
54
0
Order By: Relevance
“…Schizophrenia is now considered not to be a single disorder but a group of different biological conditions with common manifestations. In line with this, Schwarz et al (2014) found that 180 acutely ill schizophrenia patients could be classified into two distinct groups based on their serum biomarker profiles compared to the profiles of 398 control subjects. One group of patients had prominent changes in hormones and growth factors [prolactin, resistin, testosterone, insulin, platelet-derived growth factor (PDGF), leptin and angiotensinogen] whereas the other group showed mainly changes in immune or inflammatory factors [macrophage migration inhibitory factor (MIF), IL-8, IL-1RA, IL-18 and IL-16].…”
Section: Schizophreniamentioning
confidence: 58%
“…Schizophrenia is now considered not to be a single disorder but a group of different biological conditions with common manifestations. In line with this, Schwarz et al (2014) found that 180 acutely ill schizophrenia patients could be classified into two distinct groups based on their serum biomarker profiles compared to the profiles of 398 control subjects. One group of patients had prominent changes in hormones and growth factors [prolactin, resistin, testosterone, insulin, platelet-derived growth factor (PDGF), leptin and angiotensinogen] whereas the other group showed mainly changes in immune or inflammatory factors [macrophage migration inhibitory factor (MIF), IL-8, IL-1RA, IL-18 and IL-16].…”
Section: Schizophreniamentioning
confidence: 58%
“…These approaches might include development or repurposing of drugs to target inflammatory pathways, immunotherapy for antibody-associated cases of psychosis and other mental illnesses, and stratification of patients by their immune phenotype to inform treatment decisions and measure treatment response. Indeed, a 2014 molecular study 101 reported two distinct subgroups of patients with schizophrenia characterised by predominant abnormalities in either immune molecules or growth factors and hormones.…”
Section: How Might Immune Dysregulation Lead To the Manifestation Of mentioning
confidence: 99%
“…Some serum and blood-based biomarker studies have indicated sets of proteins that correlate with Sz. Examples of these are growth factors; VEGF, EGF, FGFs and cell adhesion molecule ICAM1 [87-89]. …”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%